Effects of varying water adsorption on a Cu-3(BTC)(2) metal-organic framework (MOF) as studied by H-1 and C-13 solid-state NMR spectroscopy - Gul-E-Noor, Farhana; Jee, Bettina; Poeppl, Andreas; Hartmann, Martin; Himsl, Dieter; Bertmer, Marko (Physical Chemistry Chemical Physics, 2011)
The process of water adsorption on a dehydrated Cu-3(BTC)(2) (copper (II) benzene 1,3,5-tricarboxylate) metal-organic framework (MOF) was studied with H-1 and C-13 solid-state NMR. Different relative amounts of water (0.5, 0.75, 1, 1.5, 2, and 5 mole equivalents with respect to copper) were adsorbed via the gas phase. H-1 and C-13 MAS NMR spectra of dehydrated and water-loaded Cu-3(BTC)(2) samples gave evidence on the structural changes due to water adsorption within the MOF material as well as information on water dynamics. The analysis of H-1 spinning sideband intensities reveals differences in the H-1-Cu-63/65 hyperfine coupling between dehydrated and water-loaded samples. The investigation was continued for 60 days to follow the stability of the Cu-3(BTC)(2) network under humid conditions. NMR data reveal that Cu-3(BTC)(2) decomposes quite fast with the decomposition being different for different water contents.